Virtual Reality for Distraction and Relaxation in a Pediatric Hospital Setting: An Interventional Study With a Mixed-Methods Design - Bernaerts, Sylvie; Bonroy, Bert; Daems, Jo; Sels, Romy; Struyf, Dieter; Gies, Inge; van de Veerdonk, Wessel (Frontiers in Digital Health, 2022)
Accumulating evidence supports the use of virtual reality (VR) as an effective pain and anxiety management tool for pediatric patients during specific medical procedures in dedicated patient groups. However, VR is still not widely adopted in everyday clinical practice. Feasibility and acceptability measures of clinicians’ experiences are often missing in studies, thereby omitting an important stakeholder in VR use in a clinical setting. Therefore, the aim of this mixed-methods study was to investigate the feasibility, acceptability, tolerability (primary outcomes), and preliminary effectiveness (secondary outcome) of Relaxation-VR in both pediatric patients aged 4 to 16 years and clinicians. Relaxation-VR is a VR application prototype aimed to provide distraction and relaxation for a variety of patient populations and procedures and is used to reduce anxiety, stress (tension) and pain for children in hospital. Multiple measures of acceptability, feasibility and tolerability, and pre-to-post changes in measures of pain, anxiety, stress and happiness were assessed in pediatric patients. At the end of the study, acceptability and feasibility of VR use was assessed in clinicians. Results indicate that VR use (in particular, the Relaxation-VR prototype) for both distraction and relaxation is acceptable, feasible and tolerable for a variety of pediatric patients aged 4 to 16 years, as assessed in both patients and clinicians, and can reduce anxiety, pain and tension (stress), and increase happiness in a hospital setting.